Effect of Surfactants on Kinetics and Oxidation of Decoloration of Methyl Violet and Ethyl Violet by Potassium Peroxydisulphate - M. Joshi, Hitendra; Nagar, T.N. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of methyl violet (MV) and ethyl violet (EV) by potassium peroxy disulphate (K2S2O8) have been studied colorimetrically in the presence of cationic surfactant cetyl trimethyl ammonium bromide (C16TABr), anionic sodium dodecyl sulphate (SDS) and nonionic (Triton X-100) surfactants at 30ºC. The reaction is slowed down in the presence of SDS and Triton X-100 while rate acceleration is observed in C16TABr micellar media. On the basis of kinetic results, it can be inferred that only electrostatic interactions are dominant in the case of SDS whereas hydrophobic and electrostatic interactions play an important role for C16TABr.